2021
DOI: 10.1177/0363546521990817
|View full text |Cite
|
Sign up to set email alerts
|

Early Operative Versus Delayed Operative Versus Nonoperative Treatment of Pediatric and Adolescent Anterior Cruciate Ligament Injuries: A Systematic Review and Meta-analysis

Abstract: Background: Treatment options for pediatric and adolescent anterior cruciate ligament (ACL) injuries include early operative, delayed operative, and nonoperative management. Currently, there is a lack of consensus regarding the optimal treatment for these injuries. Purpose/Hypothesis: The purpose was to determine the optimal treatment strategy for ACL injuries in pediatric and adolescent patients. We hypothesized that (1) early ACL reconstruction results in fewer meniscal tears than delayed reconstruction but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 61 publications
(72 reference statements)
2
57
1
Order By: Relevance
“…This is important because of the propensity for new meniscal tears (especially on the medial side) to occur before surgery, a trend that has been described extensively in recent literature. 1 , 6 , 21 , 31 , 37 , 38 …”
Section: Discussionmentioning
confidence: 99%
“…This is important because of the propensity for new meniscal tears (especially on the medial side) to occur before surgery, a trend that has been described extensively in recent literature. 1 , 6 , 21 , 31 , 37 , 38 …”
Section: Discussionmentioning
confidence: 99%
“…16 Similarly, ACL reconstruction within 12 weeks of injury is associated with a lower incidence of secondary meniscal injury and a higher rate of return to sports when compared to nonoperative management or delayed surgery. 17 Technical differences among adult and pediatric knee arthroscopy exist and serve as important aspects of arthroscopy education for orthpaedic residents. The pediatric knee joint is smaller in size and involves neighboring growth plates, requiring adapted techniques with miniaturized equipment.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Similarly, ACL reconstruction within 12 weeks of injury is associated with a lower incidence of secondary meniscal injury and a higher rate of return to sports when compared to nonoperative management or delayed surgery. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Current practice has evolved to favor early surgery with good functional outcomes, decreased meniscal and articular cartilage injuries, and improved rate of return to sports with minimal risk of growth disturbance. 11,14,[32][33][34][35] Surgical treatment for the skeletally immature includes physeal sparing, partial transphyseal, and transphyseal techniques. 10,12 Despite these advancements in surgical treatment, there is currently a lack of evidence-based rehabilitation protocols after ACLR specific to the youth athlete.…”
Section: Acl Injuries In Children and Adolescentsmentioning
confidence: 99%
“…skeletally immature patient, restoring knee stability, decreasing risk of subsequent injury to the knee, improving rate of return to play, and providing favorable long-term outcomes. [11][12][13][14] Although pediatric athletes return to sports at a high rate after ACL reconstruction (ACLR), 15 subsequent ACL injuries to the ipsilateral or contralateral leg are reported to be as high as 32%. 16,17 Recent studies of revision ACLR in pediatric and adolescent populations have reported lower functional outcomes, lower return to sport rates, significant risk of contralateral ACL injury, and high rates of revision graft injury 18,19 compared to primary ACLR.…”
mentioning
confidence: 99%